THE FACTORS WHICH ASSOCIATE TO THE OCCURRENCE OF PULMONARY TUBERCULOSIS FOR THE IN-PATIENT IN SCHOOLO KEYEN HOSPITAL THE SOUTHERN OF SORONG DISTRICT IN 2015 - Maria Loihala (Jurnal Kesehatan Prima, 2016)
Abstract : Tuberculosis remains one of the major killer of humans if not treated properly, the disease can cause death in almost half a case for 5 years after suffering from tuberculosis. Currently, there are 3.800 pateints who die every day or 2-3 patients die every minute because the tuberculosis. The purpose of the study is to determine the factors which are associated with a number of pulmonary tuberculosis for the in-patient in Schoolo Keyen Hospital at the southern of Sorong Distric. This research used a correlation with cross sectional. The population on the study was 54 respondents. The instrument of the study used questionnaire and time allocation of the research was held in October 2015. To collect the data on the research applied primary and secondary data. The analysis of data was conducted through univariate and bivariate. The result of statistical test by using chi-square is obtained a significant level for age variable α = 0.004<0.05, it indicates that Ho is rejected or there is a correlation between age and pulmonary tuberculosis. For occupation variable α= 0.004<0.05, it means that Ho is rejected or there is a correlation between occupation and pulmonary tuberculosis. Meanwhile, for knowledge variable α = 0.000 <0.05 shows that Ho is rejected or there is a correlation between knowledge and pulmonary tuberculosis for the in-patient in Schoolo Keyen Hospital at the southern of Sorong Distric. The conclusion of the study is there is a correlation among age, occupation and knowledge for the in-patient in Schoolo Keyen Hospital at the southern of Sorong Distric. Suggestion for Schoolo Keyen Hospital at the southern of Sorong Distric, remind and inform the management and evaluation of pulmonary tuberculosis disease, so it can improve the quality of treatment effectively to the patients with tuberculosis, in addition  health education should be enhanced, thus the patients can prevent the spread of the ailment to other family members.